Exploring medical students' assessment experience in Universiti Putra Malaysia and Maastricht University from the programmatic assessment perspectives - Adam, Siti Khadijah (2020)
Programmatic assessment differs from the traditional approach of assessment in terms of its subjective observation and emphasis on low-stake formative assessments, feedback, reflection and the use of feedback to guide future learning. The assessment approach is tailored to an individual learner and involves many assessment data points to provide a holistic judgement of the learner. Thus, this study was carried out to explore the experience of Universiti Putra Malaysia (UPM) students and Maastricht University (UM) students in relation to programmatic assessment during medical training. The similarities and differences in their perceived experience pertaining to the assessment approach were investigated. A mixed-method research design was adopted in which the Assessment Experience Questionnaire (AEQ) version 4.0 was administered to 318 UPM students and 119 UM students to gain their perceived assessment experience. Their perceptions were further explored in individual semi-structured interviews conducted with 27 UPM students and 16 UM students. The comparison of AEQ score was analysed using independent t-test in IBM SPSS Statistics software version 23. Qualitative data were analysed using thematic analysis in ATLAS.ti 8 software to generate categories and themes emerged from the interviews. Based on the analysis, it was found that the students were able to cope with their assessment demands and had intrinsic motivation to learn. UPM students were inclined to put higher learning effort and a deeper approach to learning compared to UM students. In contrast, UM students tend to be more appreciative of the value of formative assessments and have higher understanding, albeit moderately, on the standards of work required than UPM students. UPM students highlighted that they rarely received feedback, yet, they appreciated the feedback more than UM students. This study also revealed that the students from both assessment approaches were concerned with the subjectivity and fairness of their assessment system. The programmatic assessment approach was appreciated by the students for its personalised learning and relevance for professional practice. On the other hand, the traditional approach of assessment may be lacking in terms of feedback opportunities, reflective skills as well as a holistic and authentic judgement on students’ performance. Additionally, excessive volume of tasks, feedback and reflection in an assessment system may cause exhaustion to the students. The findings from this study demonstrated that assessment can cause a significant impact on the students’ learning and that their perceptions are important when designing and evaluating an assessment system.